"Burns Behind Bars": A 10-year review and cost analysis of burn injuries in prison inmates presenting to a regional burns centre, and the role of the burns outreach service. Issue 7 (November 2022) - Jawad, Ali Majeed; Nyeko-Lacek, Miriam; Brown, Liz; Javed, Muhammad Umair; Hemington-Gorse, Sarah
Highlights: Referrals from prison, a significant and challenging patient population, are rising. Most burns are scalds from assault with hot-water kettles and associated trauma. Awareness of referral criteria and first aid practice may impact outcomes. Outreach nurses are now treating inmates locally and training prison medical staff. This provides specialist care while limiting transfers and reducing overall costs. Abstract: Introduction: From 85348 inmates in England and Wales, over 26, 000 incidents of assault and 40, 000 of self-harm were reported from within prisons in 2016. This study focuses primarily on burn injuries in prison, determining the predominant aetiology as well as clinical outcomes of these injuries. Methods: Data was retrieved retrospectively and a case series performed, including all burns referred from regional prisons to our centre from 2007 to 2017 and comprising patient demographics, mechanism of injury, total body surface area affected, management, and outcome. Cost analysis of care was conducted using a previously published framework. Results: 18 cases from three regional prisons were recorded, with 67% from a single prison. Referrals rose exponentially over time, with 44% occurring in 2017. 94% were scald burns, and 56% secondary to assault, primarily through the use of kettles and mostly targeting the face and trunk. The mean TBSA of burn was 2.89% (<1–8%), and 80% received first aid. 72.2% were admitted to hospital for an average of 4 days. All burns were managed nonoperatively with dressings and underwent on average 2 outpatient reviews (1–8). Discussion: The disproportionate spread of referrals across the prisons correlates partly with the respective populations, but may also represent contrasting medical provisions. The recurring method of assault reflects the relative ease of access to hot water as a harmful agent, predominantly presenting with scalds affecting more critical areas, and with concurrent physical trauma in nearly half of cases which presents management challenges. Conclusion: Targeted education is recommended to reduce the incidence and ensure adequate management of burns in prison, referrals for which are demonstrably rising. Accordingly, the Burns Outreach team can provide training to in-house prison health staff and review referrals to specialist Burns services, aiming to ensure equitable care while alleviating costs associated with transfer to and management in hospital.